After After Tiller: the impact of a documentary film on understandings of third-trimester abortion. Issue 6 (2nd June 2016) - Sisson, Gretchen; Kimport, Katrina
Abstract: Onscreen pseudo-experiences have been shown to influence public perceptions of contested social issues. However, research has not considered whether such experiences have limits in their influence and/or vary in their impact. Using the case of third-trimester abortion, an issue subject to high amounts of misinformation, low public support and low occurrence in the general population, we investigate how the pseudo-experience of viewing After Tiller, a documentary film showing stories of third-trimester abortion, providers and patients, might serve as a counterpoint to misinformation and myth. We interviewed 49 viewers to assess how viewing the film interacted with viewers' previously held understandings of later abortion. Participants reported that viewing made them feel more knowledgeable about later-abortion patients and providers and increased their support for legal third-trimester abortion access, suggesting the efficacy of this pseudo-experience in changing belief. Nonetheless, respondents' belief systems were not entirely remade and the effects of the film varied, particularly in regards to gatekeeping around the procedure and the reasons why women seek later abortion. Findings show the potential of onscreen pseudo-experiences as a means for social change, but also reveal their limits and varying impacts.